HUBUNGAN STRATEGI MANUFAKTUR DAN BUDAYA ORGANISASIONAL Suatu Studi Empiris Pada Perusahaan Manufaktur di Indonesia - Tuty Herlina (Media Riset Bisnis & Manajemen, 2003)
This study investigates the possibility of a relationship between manufacturing strategy and organizational culture within manufacturing plants. Survey data were collected from 138 respondents in 16 plants. These plants included random samples of textile, beauty and pharmaceutical industries, which located in Jakarta, Bogor, Tangerang, and Bekasi areas. Al necessary data for this study were obtained from a questionnaire through a mail survey. The questionnaires were designed so that multiple respondents answered all perceptual ques- tions. The definition of manufacturing strategy in this study is primarily process-based, it does notinclude such content dimensions. Manufacturing strategy and organizational culture were found to exhibit a statistically significantrelationship within the plant. The analysis indicates that awell implementedmanufacturing strategy, which includes formal planning processes, com- munication of strategy, contribution to competitive position, and a long range orientation. It coexists with a dan oriented organizational cufture characterized by the use of groups and teams, low emphasis on hierarchy, and high level of loyalty and share plant-wide philosophy. This analysis suggests several implications regarding the manufacturing strategy process. First, itmay be necessary to involve mutiple decision makers at different organizational levels in the implementation of manufacturing strategy in order to help them to come up with the right decisions. Second, it may be useful to view culture as a mechanism, which controls the behavior of individuals by defining it certainly.